Analisis Kinerja Usaha Makanan Sehat Protein Bake di Kota Palembang - Tan, Richard; Alfansury, Achmad Adjie; Ong, Denise; Kasih, Yulizar (Universitas Multi Data Palembang, 2025)
This article aims to analyze the implementation of the healthy food business, Protein Bake, in Palembang City. The focus of this study includes evaluating the implemented marketing strategies, business operational effectiveness, and customer satisfaction to maintain business sustainability. The research method used is a descriptive quantitative and qualitative approach through customer surveys, interviews with business owners, and financial report analysis and sales trends from September to December 2024. The results show that digital marketing through social media and offline promotions at university cafeteria significantly contribute to business growth. Additionally, a high level of customer satisfaction is a key factor in fostering loyalty and supporting business sustainability. In conclusion, the right combination of marketing strategies and optimal customer satisfaction can strengthen competitiveness and ensure the sustainability of Protein Bake in the healthy food market.